Tipe Student Academic Support dan Academic Buoyancy pada Mahasiswa - Janice Lesmana; Jane Savitri (Universitas Kristen Maranatha, 2019)
This study aims to overview the relationship between student academic support (informational, esteem, motivational and venting support) and academic buoyancy in students. 230 participants were selected used proportionate stratified random sampling technique. This study used a modified Student Academic Support Scale (SASS; Thompson & Mazer, 2009) and modified Academic buoyancy Scale (ABS; Martin & Marsh, 2008), correlated using Spearman’s correlation test. The results show that academic buoyancy has a significant positive relationship with esteem support (r = 0.168; p = 0.011), motivational support (r = 0.212; p = 0.001) and venting support (r = 0.158; p = 0.017), but doesn’t have relationship with informational support (r = 0.105; p = 0.111). Researcher suggests to do further research about contribution students' academic support to academic buoyancy. It is recommended to develop a mentoring program for students that facilitates mutual helping, care and motivating between students in the academic. Keywords: Student Academic Support, Academic buoyancy